2016
DOI: 10.1177/0333102416644436
|View full text |Cite
|
Sign up to set email alerts
|

Migraine-tic syndrome: Two further case reports

Abstract: Background Migraine-tic syndrome was first reported in 2004 in a 44-year-old woman who had concomitant symptoms of both typical trigeminal neuralgia and migraine. We report here two further cases of migraine-tic syndrome and speculate on the relevance of this condition to the pathophysiology of headache. Case reports A 43-year-old woman presented with typical trigeminal neuralgia symptoms that preceded the onset of migraine headache; both headache types responded to treatment with sumatriptan. A 35-year-old wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, with a simple coincidence rule, TN should more commonly occur with migraine or TTH. Very recently, Hinze et al 3 reported that there are just three cases of migraine-tic syndrome in the literature. Although a recent study indicates that migraine is a risk factor for the development of TN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, with a simple coincidence rule, TN should more commonly occur with migraine or TTH. Very recently, Hinze et al 3 reported that there are just three cases of migraine-tic syndrome in the literature. Although a recent study indicates that migraine is a risk factor for the development of TN.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, the coexistence of two rare primary headaches is scarce. 2 Trigeminal neuralgia (TN) has been reported with various other primary headaches such as migraine (migraine-tic syndrome), 3 cluster headache (clustertic syndrome), 4,5 and paroxysmal hemicrania (paroxysmal hemicrania-tic syndrome). [6][7][8] TN may also be associated with short-lasting unilateral neuralgiform headache with conjunctival injection and tearing (SUNCT) and short-lasting unilateral neuralgiform headache attacks with cranial autonomic symptoms (SUNA).…”
Section: Introductionmentioning
confidence: 99%